ANALISIS PENGHAMBAT PENERAPAN BUILDING INFORMATION MODELING (BIM) PADA KONTRAKTOR DI KOTA DENPASAR - Nodya Dharmastika; Gede Suranata, Putu; Cri Vinantya Laksmi, Ida Ayu (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2024)
ABSTRACT Technological developments in the construction industry have led to digitalization. One of them is the construction industry starting to implement Building Information Modeling (BIM). BIM is a system for managing information into building models in digital form. BIM processes input into information in the form of building modeling as an aid in the decision-making process at each stage of a construction project. In its application, BIM is still not optimal and has many obstacles. Of the 68 contractors in the city of Denpasar, only 3 contractors have used BIM in implementing their construction projects. Therefore, it is necessary to carry out a study to find out the factors that hinder the implementation of BIM among contractors in the city of Denpasar. The data collection method was carried out using a closed questionnaire which was distributed to 68 contractors in the city of Denpasar. The collected data was analyzed using Principal Component Analysis (PCA) factor analysis. The analysis carried out produced 3 factors that hindered the implementation of BIM in the city of Denpasar. These 3 factors include: difficulty in starting to implement BIM, high costs in implementing BIM, BIM is not a target for contractors. The third factor, namely that BIM is not the contractor's target, is the most dominant factor with the highest mean data value of 3.907. Keywords: Building Information Modeling (BIM); Obstacle Factor; Contractor; Factor Analysis